A single amino acid substitution in puroindoline b impacts its self-assembly and the formation of heteromeric assemblies with puroindoline a. (July 2015) - Geneix, Nathalie; Dalgalarrondo, Michèle; Bakan, Bénédicte; Rolland-Sabaté, Agnès; Elmorjani, Khalil; Marion, Didier
Abstract: Puroindolines (PINs) A and B were purified from soft (Paledor) and hard (Recital, Courtot) wheat cultivars. Their purity and heterogeneity due to post-translational processing were characterized by SDS- and acid-PAGE, reversed-phase HPLC and mass spectrometry. By using dynamic light scattering (DLS), asymmetrical flow field-flow fractionation (AF4) and size exclusion chromatography (SEC), we showed that the size distributions of PINA are similar for the three varieties and that, in solution, they self-assembled into small aggregates, mainly dimers. Conversely, PINB isolated from hard varieties (PINB-D1b and PINB-D1d) are assembled into large aggregates while PINB-D1a formed small aggregates, mainly monomers. Mixed solutions of PINA and PINB formed heteromeric aggregates. The large PINB-D1b aggregates were retained even at a high (4:1) PINA/PINB weight ratio. Reversible dissociation of large aggregates into small aggregates suggested that weak interactions control the self-assembly of PINs. The aggregative properties of PINs have now to be taken into account when studying their interactions with other components to decipher the causal relationships between these proteins and grain hardness. Highlights: Differences of puroindoline post-translational processing was observed in wheat cultivars. PINA self-assembled in small aggregates, mainly dimers, in solution. A single mutation on puroindoline b impacted its self-assembly. Puroindoline b single mutation interfered on the self-assembly of puroindoline a.